Impact of image feature selection on retrieval accuracy - Muhammad Hayat Khan, Sumaira; Hussain, Ayyaz (International Journal of Engineering and Technology, 2018)
Two main approaches for retrieving a required image from a database are known as the local approach and the global approach. Each method is named based on the type of feature extraction technique used and the calculation of the feature vector. This paper proposes content based image retrieval technique at local level incorporating all the rudimentary features. Retrieval results of the proposed method are compared to find the optimal approach to image retrieval. The proposed system is also evaluated by comparing their experimental results with some state of the art system in the literature.Â Â Â